Tissue-Specific GHR Knockout Mice: An Updated Review - Nagarajan, Akash; Srivastava, Hemant; Jablonsky, Joseph; Sun, Liou Y. (Frontiers in Endocrinology, 2020)
Growth hormone (GH) signaling plays a key role in mediating growth, development, metabolism, and lifespan regulation. However, the mechanisms of longevity regulation at the cellular and molecular level are still not well-understood. An important area in the field of GH research is in the development of advanced transgenic systems for conditional expression of GH signaling in a cell type- or tissue-specific manner. There have been many recent studies conducted to examine the effects of tissue-specific GHR disruption. This review updates our previous discussions on this topic and summarizes recent data on the newly-made tissue-specific GHR-KO mice including intestinal epithelial cells, bone, hematopoietic stem cells, cardiac myocytes, and specific brain regions. The data from these new genetically-engineered mice have a significant impact on our understanding of the local GH signaling function.